Synthetic peptides representing two protective, linear B-cell epitopes of outer membrane protein F of Pseudomonas aeruginosa elicit whole-cell-reactive antibodies that are functionally pseudomonad specific. - Gilleland, L B (1995)
Peptide 9 (TDAYNQKLSERRAN) and peptide 10 (NATAEGRAINRRVE) represent surface-exposed epitopes of outer membrane protein F of Pseudomonas aeruginosa. Rats immunized with four intramuscular inoculations on days 0, 14, 28, and 42 with either peptide 9 or peptide 10 conjugated to keyhole limpet hemocyanin were afforded protection against pulmonary lesions when examined 7 days subsequent to challenge (day 56) via intratracheal inoculation of P. aeruginosa-containing agar beads. Peptide 9 shares considerable homology with other OmpA-related outer membrane proteins in various bacteria, whereas peptide 10 displays little homology with these other proteins. Antisera directed to peptide 9 reacted weakly with cell envelope proteins from the various other OmpA-associated bacteria upon immunoblot analysis. However, antisera directed to peptide 10 reacted only with Neisseria gonorrhoeae cell envelope proteins upon immunoblot analysis. Antisera to both peptides 9 and 10 reacted at minimal titers with whole cells of the various other bacteria in a whole-cell enzyme-linked immunosorbent assay (ELISA) but antisera to each of the peptides reacted at high titers when various strains of P. aeruginosa were used as the ELISA antigen. Antibodies to peptides 9 and 10 were protective, reactive to all strain of P. aeruginosa tested except for a protein F-deficient mutant, and functionally specific against pseudomonads.